Adhesion characteristics and stability assessment of lectin-modified liposomes for site-specific drug delivery - EHRHARDT, CARSTEN (My University, 2008)
Carbohydrate moieties of the cellular glycocalyx have been suggested to play an important role in biological recognition processes during pathologic conditions, such as inflammation and cancer. Herein, we describe lectin-modified liposomes which might have potential for site-specific drug delivery during the therapy of such diseases. Specific interactions of plain (i.e., unmodified) and PEGylated, lectin-grafted liposomes with model membranes were investigated under real-time flow conditions using a quartz crystal microbalance. In addition, the morphology of the liposomal systems was assessed by atomic force microscopy. Plain liposomes exhibited only unspecific adhesion to glycolipid membranes and had a tendency to coalesce. The degree of membrane interaction was significantly increased when plain liposomes were modified with the lectin, Concanavalin A. However, vesicle fusion also markedly increased as a result of lectin modification. Additional PEGylation of liposomes reduced unspecific adhesion phenomena, as well as coalescence. Moreover, our studies enabled us to establish quartz crystal microbalance and atomic force microscopy as powerful and complementary methods to characterize adhesion properties of targeted drug delivery systems.
PUBLISHED
Keywords: Atomic force microscopy; Drug targeting; Concanavalin A; Quartz crystal microbalance; PEGylation; Glycocalyx